Análise do albedo em áreas de caatinga preservada e substituída por pastagem - Souza, Alcindo Mariano de (2022)
The caatinga is one of the endemic biomes most vulnerable to climate change. Studies of the consequences of changes in biophysical factors, among them the surface albedo, are relevant to understand the role of this biome in the climate of the Northeast Region of Brazil. Understanding the processes that lead to albedo changes through analysis in caatinga areas can help in the preservation and more appropriate use of its resources. In this perspective, a comparative analysis between the albedo of a preserved caatinga area and another one anthropized in pasture with grazing management brings important information for the perception of possible consequences of land use and helps in the understanding of degradation and contributes to the preservation of the biome. Also important are information on the potential of using albedo in grasslands as a climate change mitigation strategy through Solar Radiation Management (SEM). Thus, the study was conducted from observations of the components of the net radiation at the surface in two environments: Seridó Ecological Station considered as preserved caatinga (Caatinga), located in the municipality of Serra Negra do Norte and; Jundiaí Agricultural School considered caatinga replaced by pasture with management (Pasture), in Macaíba, both in the state of Rio Grande do Norte. The albedo data comprised an annual rainfall cycle within four periods: the dry season, the transition between dry and rainy, rainy, and the transition between rainy and dry in both Caatinga and Pasture. The albedo averages were higher in the Pasture in all seasons, with a value of 0.18 in the annual cycle, showing little seasonal variability. In the Caatinga, the albedo average was 0.15, with the rainy to dry transition season being the one with the highest value and equal to 0.16. The biggest difference in the average albedo between the Pasture and the Caatinga happened in the dry season and the smallest in the rainy season and in the transition between dry and rainy season. Although the precipitation in the period was higher in the pasture with 992.7 mm, it still had a higher average albedo compared to the Caatinga, which had a cumulative precipitation of 507.6 mm in the period. The average solar elevation was also higher in the Pasture, which would influence the reduction of the difference between the average albedo in relation to the Caatinga. However, the albedo based on the daily mean values was not significantly influenced by the solar elevation. Regarding the average albedo at each time of day, there was a strong negative correlation for all seasons in the Pasture, also showing a greater amplitude in the albedo variation throughout the day in relation to the Caatinga. For both experimental sites, the greatest dispersions in the frequencies of the hourly mean values of albedo occurred in the early morning and late afternoon, with greater regularity at times close to noon. Some of the consequences of this study are: the confirmation that an area of caatinga replaced by pasture acquires biophysical characteristics that imply a reduction in net radiation compared to caatinga with native forest, even in pastures with grazing management and with selected forage and; that a region where pasture is managed reduces albedo variability, especially in the comparison between its dry and rainy seasons, pasture management avoids an excessive reduction in vegetation cover and these forages do not allow a much larger increase in albedo, especially in the dry season. This smaller seasonal variability when compared to the Caatinga, even though they are very close, depending on the coverage area, may be more relevant for the net radiation and the climate of the region. The most significant response of the mean hourly albedo to solar elevation and its highest value average, even with greater precipitation, in the Pasture point to the potential use of albedo in the management of reflected solar radiation, however further investigations may indicate the possibility of its use in reducing of the local temperature, mainly in warmer periods during the dry season.